2023
DOI: 10.1038/s41440-023-01176-3
|View full text |Cite
|
Sign up to set email alerts
|

Emerging topics on basic research in hypertension: interorgan communication and the need for interresearcher collaboration

Abstract: The pathogenesis of hypertension is multifactorial and highly complex. Basic research plays critical roles in elucidating the complex pathogenesis of hypertension and developing its treatment. This review covers recent topics in basic research related to hypertension in the following six parts: brain/autonomic nervous system, kidney, vascular system, potential treatments, extracellular vesicles, and gut microbiota. The brain receives afferent nerve inputs from peripheral organs, including the heart, kidneys, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Hypertension research to date has primarily focused on defects in the blood vessels, kidneys, and brain; and the various neurotransmitters and hormones involved. [7][8][9][10] Although the experimental evidence for the roles of abnormalities in these systems in the development of hypertension is indisputable, recent studies have revealed that other systems, such as the gut and skin, also play roles in the development of hypertension. [11][12][13][14][15] In this review, we discuss the contribution of skin function to blood pressure regulation.…”
mentioning
confidence: 99%
“…Hypertension research to date has primarily focused on defects in the blood vessels, kidneys, and brain; and the various neurotransmitters and hormones involved. [7][8][9][10] Although the experimental evidence for the roles of abnormalities in these systems in the development of hypertension is indisputable, recent studies have revealed that other systems, such as the gut and skin, also play roles in the development of hypertension. [11][12][13][14][15] In this review, we discuss the contribution of skin function to blood pressure regulation.…”
mentioning
confidence: 99%